Assessment of knowledge, attitude and anxiety among junior resident doctors in India during COVID-19 Pandemic - Sahya S. Dev; Joe Abraham; Rahul S. Pillai (College of Community Physicians of Sri Lanka, 2023)
Introduction: Healthcare workers were the frontline defence against the COVID-19 pandemic, especially the junior resident doctors, and were among those at the highest risk of acquiring the disease. Disease transmission among them was worsened by overcrowding, lower work force, lack of isolation facilities, lack of standard quality personal protection equipment, contaminated environment and inadequate knowledge and practice of infection control practices. Objectives: To assess the knowledge, attitude and anxiety among junior resident doctors in India with respect to COVID-19 Methods: A cross-sectional study was conducted during August-October 2020 among 451 junior resident doctors in India. A validated 35-item questionnaire was distributed to the participants using social media platforms. The snowball sampling technique was used. Results: A total of 451 junior resident doctors were included as study participants, of whom 52.3% were women. More than 90% of them had a good level of knowledge regarding COVID-19.Almost allof the participants believed that wearing masks (98%) and keeping social distance (100%) would reduce the risk of COVID-19 transmission, but that government regulations were insufficient to combat the disease (63%). The level of anxiety among study participants was on the higher side. Conclusions & Recommendations: The level of anxiety among the junior resident doctors was relatively high. Therefore, mental and psychological support is crucial for them, and in turn, essential for effective management of the health crisis.